Paths for Location: Home(s) in Loida Maritza Pérez’s Geographies of home - Morais, Juliana Borges Oliveira de (Em Tese, 2011)
Geographies of home portrays a Dominican family who has immigrated to the United States. Home is presented in numerous ways by the women characters, pointing to a fluid rather than a fixed concept in the novel. Aurelia and Iliana are the objects of this analysis.